2006
DOI: 10.2190/7ucu-8f9m-94qg-5wwq
|View full text |Cite
|
Sign up to set email alerts
|

Balancing Work and Academics in College: Why Do Students Working 10 to 19 Hours per Week Excel?

Abstract: Given that 74% of undergraduates work an average of 25.5 hours per week while going to school, we know surprisingly little about how off-campus employment affects undergraduates and to what extent its impact varies by the number of hours worked. Our survey of undergraduates at a small liberal arts college found that the academic performance of students who worked off-campus was comparable to nonworkers. Notably, the academic performance (greater hours studied and higher grades) of students who worked 10-19 hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
71
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(76 citation statements)
references
References 4 publications
(2 reference statements)
1
71
0
4
Order By: Relevance
“…According to the 2003-2004 National Postsecondary Student Aid Survey (NPSAS), more than two thirds of students at 4-year institutions are employed in on-or off-campus jobs while enrolled, with 23% working full-time and 47% working part-time. The main reasons often cited for working are the need for spending money, to finance basic living expenses, and to assist in paying their tuition (Dundes & Marx, 2006). Students also report that working offers a chance to identify future career options, enhance their interpersonal and time management skills, create networking opportunities, and connect to the society (Cheng & Alcantara, 2007).…”
Section: Time Allocated To Employment-related Activitiesmentioning
confidence: 99%
“…According to the 2003-2004 National Postsecondary Student Aid Survey (NPSAS), more than two thirds of students at 4-year institutions are employed in on-or off-campus jobs while enrolled, with 23% working full-time and 47% working part-time. The main reasons often cited for working are the need for spending money, to finance basic living expenses, and to assist in paying their tuition (Dundes & Marx, 2006). Students also report that working offers a chance to identify future career options, enhance their interpersonal and time management skills, create networking opportunities, and connect to the society (Cheng & Alcantara, 2007).…”
Section: Time Allocated To Employment-related Activitiesmentioning
confidence: 99%
“…A large body of research has found that on-campus, part-time employment of 10-19 hours per week tends to have a positive influence on academic performance (Astin, 1975, Dundes & Marx, 2006. However, studies have shown that working long hours (more than 20/week) off-campus adversely impacts academic success, retention, and a student's ability to become involved with campus activities and engaged with faculty and peers (Ehrenberg & Sherman, 2008;Furr & Elling, 2000).…”
Section: Implications For Retentionmentioning
confidence: 99%
“…According to Dundes and Marx (2006), 38% of students in their study worked 20 or more hours per week in an effort just to pay tuition. Of the students who worked 20 or more hours per week, 82% did so just to meet basic living expenses.…”
Section: Implications For Retentionmentioning
confidence: 99%
“…Research on the work-dropping out connection tends to show that there is a U-shaped relationship between the likelihood of dropping out and the number of hours worked outside school, with a higher exit rate or poorer academic performance evidenced by both non-working students and by students whose hours of work pass a critical threshold. This U-shaped relationship is observed in the USA (Dundes and Marx 2006;Mortimer 2003, Riggert et al 2006Stern and Briggs 2001), in the UK (McKechnie and Hobbs 2001), in France (Beaupère et al 2007;Beffy, Fougère, and Maurel 2009;Bérail 2007) and in Canada (Bowlby and McMullen 2002;Bushnik 2003).…”
mentioning
confidence: 90%